Electronic Auctions and the Constitutional Right to Public Services in Indonesia: A Legal Evaluation of KPKNL Practices - Febrianto, Surizki; Muslikhah, Umi; Binti Aminudin, Rabiah; Adi, Moses (Universitas Islam Negeri Raden Intan Lampung, 2025)
The digitalization of public services has positioned state auctions as an integral part of constitutionally guaranteed public service delivery. In Indonesia, the implementation of electronic auctions (e-auction) by the Directorate General of State Assets (DJKN) through the State Assets and Auction Service Office (KPKNL) represents the state’s obligation to provide transparent, accountable, and legally certain public services. This study examines the regulation of electronic auctions, particularly the implementation of Minister of Finance Regulation Number 86 of 2024, from the perspective of the constitutional right to public services as guaranteed under Article 28D paragraph (1) and Article 34 paragraph (3) of the 1945 Constitution and Law Number 25 of 2009 on Public Services. Using a legal research method that draws on statutory, conceptual, and case approaches, this study analyzes KPKNL's auction regulations, court decisions, and administrative practices. The findings indicate that PMK No. 86 of 2024 strengthens legal certainty, transparency, and accountability in electronic auction services by reinforcing the evidentiary status of auction minutes and standardizing procedural safeguards. However, empirical evidence shows that the fulfillment of constitutional public service rights remains constrained by administrative rigidity, information asymmetry, and limited access to legal remedies for service users. This study concludes that while electronic auction regulations improve public service quality, further alignment with constitutional principles of equality before the law, legal certainty, and accountable digital services is necessary to realize citizens’ constitutional right to public services fully.